The truth and the essence of the intuitive consciousness-observational procedures - Popović, Brankica V. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
The purpose of Husserls principles of phenomenology consists in showing the way in which transcendental subjectivity can only be brought to self-administration. If someone wants to expose the logical notation, he should go beyond the meaning of words, which are always ambiguous. This phenomenon must be considered in light of its origin in a conscious life, whose activity is theoretical. This statement contains a grain of Husserl's profound philosophical principles, the first principles of phenomenology, according to which the concept of being so closely associated with the concept of experience that brings the last justification for logical methods. Namely, we can justify giving the courts that have ontological value and only then can we be sure that we have a reflection of not only being present, but just to be.